The concept of implementation of individual education plans for students with special educational needs visual impairment - Mohd Norazmi Nordin; Syamsul Azizul Marinsah; Yusmi Mohd Yunus; Nor Fauziyana Mosbiran (Obstetrics & gynaecology forum, 2024)
An Individual Education Plan is a teaching plan made to meet the needs of specific students. The RPI between each student is different because the plan made is based on the meeting, goals, level of ability and academic functioning of the student. This RPI is very important in determining the continuation of learning for students with special needs at school. An accurate and relevant lesson plan for each student is able to provide them with the education they deserve. Considering the variety of levels and categories of special education faced, RPI is the best initiative that can be given to MBPK to determine their development more specifically. Good and specific RPI planning according to MBPK's ability level can change the negative behavior of students and can help them focus on academics better. Structured and functional RPI planning needs to be done for MBPK with speech problems as early as possible so that students can speak well and help students communicate with other students. Effective implementation of RPI at the initial stage is also necessary to avoid other problems arising such as social problems caused by students not knowing how to communicate with friends